2014
DOI: 10.7314/apjcp.2014.15.6.2523
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Postoperative Stimulated Thyroglobulin Level at the Time of131I Ablation Therapy for Differentiated Thyroid Cancer

Abstract: Background: Serum thyroglobulin detection plays an essential role during the follow-up of thyroid cancer patients treated with total/near total thyroidectomy and radioiodine ablation. The aim of this retrospective study was to evaluate the relationship between stimulated serum thyroglobulin (Tg) level at the time of high dose 131 I ablation and risk of recurrence, using a three-level classification in patients with differentiated thyroid cancer (DTC) according to the ATA guidelines. Also we investigated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Although there was a study concluded that the stimulated serum Tg level at 1 st RAI therapy may not determine risk of recurrence (Hasbek, 2014). Our study, in agreement with some studies (Lin et al, 1998;Verburg et al, 2005), shows that stimulated serum Tg level at 1 st RAI therapy was an another independent prognostic factor for successful RAI therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Although there was a study concluded that the stimulated serum Tg level at 1 st RAI therapy may not determine risk of recurrence (Hasbek, 2014). Our study, in agreement with some studies (Lin et al, 1998;Verburg et al, 2005), shows that stimulated serum Tg level at 1 st RAI therapy was an another independent prognostic factor for successful RAI therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Even after successful total thyroidectomy by applied experienced surgeons, absence of residual thyroid tissue is extremely rare. Low serum Tg levels (<2 ng/ml) predict successful ablation and remaining no residual tumor tissue after ablation;[9] however, the current study revealed that the postoperative Tg level is not related to ablation success as all patients with low and high levels achieved successful ablation that could be explained by 92% of patients are in the ATA low-risk category. Regarding the AJCC staging system, it was accurate to predict recurrence or persistence of disease in our population.…”
Section: Discussionmentioning
confidence: 62%
“…Postoperative RAI ablation is routinely used at some institutions to destroy thyroid remnant and occult foci of neoplastic cells. [9] Low serum sTg level at the time of ablation has negative predictive value for the absence of residual disease and the risk of persistent disease increases with increased sTg levels. [10] In this retrospective study, we investigated the natural course of DTC in 100 patients whose initial assessment after primary treatment (near-total thyroidectomy and RRA) revealed TSH-stimulated serum Tg levels between 0.4–170 ng/mL with complete structural response.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroglobulin (Tg) is often used to monitor the recurrence of papillary thyroid carcinoma (13,14); therefore, changes in serum Tg levels before and after PLA should also be evaluated. Increased serum Tg levels after 131 I treatment are indicative of recurrence or lymphatic metastasis (15,16). The aim of this study was to investigate and describe the use of conventional ultrasound and CEUS combined with serum Tg measurements for the assessment of PLA treatment of cervical metastatic lymph node metastases from papillary thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%